Analysis of the correlation between p53 and bcl-2 expression with staging and prognosis of the colorectal adenocarcinoma - Lustosa,Suzana Angelica Silva (2005)
PURPOSE: To analyze the correlation between p53 and bcl-2 expression and colorectal adenocarcinoma staging and prognosis. METHODS: This was a retrospective series of 125 colorectal adenocarcinoma patients (67 women and 58 men; ages 30-87 years) who underwent surgery with curative intent. The mean follow-up was 28.5 months (range: 2-96 months). TNM staging, tumor recurrence, survival and cancer-related mortality were analyzed. Immunoreactivity was evaluated using DO7 (Dako) for p53 and K492 (Dako) for bcl-2. Tumors with accumulation of staining for cytoplasmic bcl-2 or nuclear p53 in more than 10% of cells were considered positive. Statistical analysis utilized Pearson chi-squared, log-rank and Wilcoxon tests, and Kaplan-Meier survival estimation (significance level: p<0.05). RESULTS: p53+ was found in 11.8% (14/118), bcl-2+ in 50% (58/116) and associated p53+/bcl-2+ in 6.4% (7/109) of the tumors. There was no significant correlation between expression of these biomarkers and TNM I, II, III and IV staging (p=0.385 for p53; p=0.461 for bcl-2). For tumor recurrence, p53+ was found in 9.5% (2/21), bcl-2+ in 50% (11/22), and associated p53+/bcl-2+ in 5.2% (1/19) of the tumors (p=0.714, p=1.000 and p=0.960, respectively). For survival analysis, p53+: 57 months (45.0-68.0), bcl-2+: 78 (37.0-89.0), and p53+/bcl-2+: 62 (56.0-68.0) (p=0.319). For cancer-related mortality, p53+: 8.3% (3/36), bcl-2+: 47.2% (17/36), and p53+/bcl-2+: 5.9% (2/36) of the patients (p=0.432, p=0.688 and p=0.907, respectively). CONCLUSION: No correlation was found between tumor expression of p53 and bcl-2 and the TNM staging, recurrence, survival and cancer-related mortality in colorectal adenocarcinoma.